Q. 18

If x + y =

Answer :

    (x - y) 2 = x2 - 2xy + y2
                 = x2 + 2xy + y2 -
4xy
                 =
(x + y)2 - 4xy 
                 = 52 - 4 × 4
             = 25 - 16 = 9
 ∴  x – y = 𢆩
            = 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses